Tourist Zones, Their Types and Economic-Social Significance - qizi, Saydaliyeva Umidaxon Solijon (International Journal on Integrated Education, 2023)
In this article, on the example of the countries of the world, the concept of a tourist zone, its types, legal foundations, organizational and economic mechanisms, advantages, positive and negative aspects in the development of the territory, the management system are considered.